Levantamiento e implementación de procesos de información aplicando la metodología de biblioteca de infraestructura de tecnologías de información, en el Centro de Tecnologías de la Información del Gobierno Autónomo Descentralizado Municipal del cantón Latacunga, en el período 2015 – 2016 - Vega Luzpa, Edison Fabián (2016)
This project is made in order to lift and implement processes and procedures at the Center for Information Technology of the Autonomous Government Decentralized Municipal Latacunga Canton (GAD-MCL), so that an analysis of the situation was carried out using the SWOT for the respective diagnosis. Subsequently, a study of the theoretical basis of the methodology Infrastructure Library Information Technologies, which accompanies and underpins the process definition and implementation of the methodology was made, also was investigated on development technologies used in the GAD-MCL ….